Coronavirus Infection in Hematopoietic Stem Cell Transplant Recipients. (4th October 2017) - Eichenberger, Emily; Satlin, Michael; Zappetti, Dana; Small, Catherine; Shore, Tsiporah; Van Besien, Koen; Soave, Rosemary
Abstract: Background: Hematopoietic stem cell transplants (HSCT) recipients are at increased risk of respiratory viral infections and their associated complications. Although the epidemiology of many respiratory viruses has been well characterized in this population, little is known about the epidemiology of human coronavirus (HoCV) infection. Methods: We identified HSCT recipients with symptoms of a respiratory tract infection who tested positive for HoCV by nasopharyngeal (NP) swab from January 2013 to December 2016 at our hospital. NP swabs were analyzed by the FilmArray® Respiratory Panel, which detects 17 respiratory viruses, including 4 coronavirus serotypes. We reviewed the demographics, transplant type, comorbidities, smoking status, respiratory symptoms, co-pathogens, and radiographic findings of infected patients. We then assessed the incidence of developing a lower respiratory tract infection (LRTI), defined as new pulmonary infiltrates or detection of HoCV in bronchoalveolar lavage fluid, within 30 days of initial diagnosis. Results: We identified 58 HSCT recipients who tested positive for HoCV. The median patient age was 54 years, 29 (50%) were men, and 24 (41%) were current or prior smokers. Fifty (86%) patients had received an allogeneic HSCT and 8 (14%) had received an autologous HSCT. The coronavirus serotypes were: OC43 ( n = 19, 33%), NL63 ( n = 18, 31%), HKU1 ( n = 16, 28%), and 229E ( n = 5, 9%). The median time from transplant until detection of HoCV infection was 135 days (IQR=256). Seventeen (29%) patients were lymphopenic at the time of diagnosis and 17 (29%) were receiving corticosteroids. The most common initial symptoms were cough ( n = 41, 71%), rhinorrhea ( n = 31, 53%), and dyspnea ( n = 17, 29%), and 19 (33%) and 16 (28%) patients had fever and hypoxia, respectively. Seventeen patients (29%) developed a LRTI within 30 days of diagnosis and 43% harbored a co-pathogen in the blood or respiratory tract. Three patients (5%) were intubated for respiratory failure and 1 (2%) died within 30 days. Conclusion: HoCV infection is common in HSCT recipients and is caused by multiple serotypes. Nearly one-third of patients have fever and hypoxia upon initial diagnosis or progress to LRTI. Further research is needed to identify risk factors for HoCV LRTI in this population. Disclosures: All authors: No reported disclosures.